Determinants of Bribery in International Business: The Cultural and Economic Factors - Sanyal, Rajib (Journal of business ethics, 2005)
Corruption Perceptions Index (CPI) scores for 47 countries reported by Transparency International were used to ascertain determinants of bribe taking in international business. Two sets of independent variables – economic and cultural – were used in a multiple regression analysis. Results indicate that bribe taking was more likely to be prevalent in countries with low per capita income and lower disparities in income distribution. Cultural factors such as high power distance and high masculinity in a country were also likely to be associated with high level of bribe taking. Both economic and cultural factors were important explanatory factors of bribery. Implications of the findings for combating bribery are discussed.